A Public Sector Marketing Model to Measure the Social and Environmental Values of Public Strategies: An Empirical Study on a Green Public Service. Issue 2 (2nd April 2016) - Boenigk, Silke; Möhlmann, Mareike
ABSTRACT: This article develops a public sector marketing model to measure the social and environmental values of public strategies. Applying partial least squares path modeling, the authors empirically test the model by conducting a quantitative survey (N = 603) among users of a green public service in the form of a public bike-sharing system. The findings reveal that users simultaneously perceive public outcomes on the social value and environmental value dimensions. The effect estimated on the perceived social value dimension of the green public service was slightly stronger than the effect on the environmental value dimension. Thus, users primarily perceive self-centered values, before considering values generated for the environment. The findings also show that engaging citizens now in the actual usage of green public services can foster green consumption intentions in the future.